2018
DOI: 10.1186/s40659-018-0206-3
|View full text |Cite
|
Sign up to set email alerts
|

A thermophilic microorganism from Deception Island, Antarctica with a thermostable glutamate dehydrogenase activity

Abstract: BackgroundThe Antarctic continent is a source of extreme microorganisms. Millions of years of isolation have produced unique biodiversity with adaptive responses to its extreme environment. Although the Antarctic climate is mainly cold, the presence of several geothermal sites, including thermal springs, fumaroles, hot soils and hydrothermal vents, provides ideal environments for the development of thermophilic and hyperthermophilic microorganisms. Their enzymes, called thermoenzymes, are the focus of interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Cultured bacterial isolates belonging to Geobacillus, Bacillus, Brevibacillus , and Thermus were explored and showed positives results for the production of lipases ( Muñoz et al, 2013 , 2015 ). Flores et al (2018) partially characterized a thermophilic microorganism identified as Bacillus gelatini , which showed stable glutamate dehydrogenase activity at high temperatures. Additionally, a new thermophile identified as Albidovulum sp.…”
Section: Introductionmentioning
confidence: 99%
“…Cultured bacterial isolates belonging to Geobacillus, Bacillus, Brevibacillus , and Thermus were explored and showed positives results for the production of lipases ( Muñoz et al, 2013 , 2015 ). Flores et al (2018) partially characterized a thermophilic microorganism identified as Bacillus gelatini , which showed stable glutamate dehydrogenase activity at high temperatures. Additionally, a new thermophile identified as Albidovulum sp.…”
Section: Introductionmentioning
confidence: 99%
“…Springs in Greenland (Denmark) are heated to 55–62 °C [ 10 ]. A few geothermal sites with temperatures ranging from 50 to 95 °C were found in the Southern Hemisphere in Antarctica [ 11 , 12 ]. At the same time, the temperature of water in the hottest CHS reaches 94–97 °C [ 2 , 3 ], making CHS, to our knowledge, the hottest documented geothermal springs in the Northern Hemisphere permafrost zone.…”
Section: Introductionmentioning
confidence: 99%
“…Few previous works focused on cyanobacterial mats and the diversity of phototrophic organisms [ 9 , 10 , 13 ] in hydrothermal springs with temperatures below 62 °C, where the illumination plays a crucial role in the establishment of microbial communities. Studies of the prokaryotic diversity of Antarctic hot environments revealed the presence of Geobacillus , Bacillus , Brevibacillus , Thermus , Thermococcus, and Pyrococcus members [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other geothermal areas worldwide ( e.g. , Miller et al , 2009; Wang et al , 2013; Sharp et al , 2014), the microbial community present in Deception Island is weakly characterized, with few studies focused on the isolation of thermophilic and psychrophilic bacteria (Carrión et al , 2011; Muñoz et al , 2011; Bendia et al , 2018a) with potential use for biotechnological applications (Flores et al , 2018). The coexistence of microorganisms with different thermal and metabolic traits (ammonia oxidation, sulfur reduction, and methanogenesis) was attributed to the steep physicochemical gradients (temperature and geochemical) across the island (Fermani et al , 2007; Bendia et al , 2018b, 2018a).…”
Section: Introductionmentioning
confidence: 99%